1989
DOI: 10.1111/j.1600-0528.1989.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of xylitol chewing gum on dental caries

Abstract: About 85% (n = 269) of the subjects who participated in the Ylivieska follow-up studies on the effect of xylitol chewing gum on dental caries during 1982-84 or 1982-85 were re-examined in 1987 for the analysis of possible long-term preventive effects. Further caries reduction was found 2 or 3 yr after the discontinuation of the use of xylitol. The effect was especially marked in girls; the reduction in caries increment in the post-use years was 60% for the 2-yr users, suggesting that more pronounced caries red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 15 publications
(19 reference statements)
3
47
0
Order By: Relevance
“…The reversals were already reported in the Turku Sugar Studies [Scheinin and Mäkinen, 1975], and they seemed to also appear in this field study. The remineralization effect of xylitol has been reported in several clinical studies [Scheinin and Mäkinen, 1975;Galliunin, 1981;Scheinin et al, 1985;Kandelman et al, 1988;Isokangas et al, 1989;Kandelman and Gagnon, 1990;Mäkinen et al, 1995b] and documented by clinical photographs on advanced dentinal caries lesions by Mäkinen et al [1995b].…”
Section: Discussionmentioning
confidence: 99%
“…The reversals were already reported in the Turku Sugar Studies [Scheinin and Mäkinen, 1975], and they seemed to also appear in this field study. The remineralization effect of xylitol has been reported in several clinical studies [Scheinin and Mäkinen, 1975;Galliunin, 1981;Scheinin et al, 1985;Kandelman et al, 1988;Isokangas et al, 1989;Kandelman and Gagnon, 1990;Mäkinen et al, 1995b] and documented by clinical photographs on advanced dentinal caries lesions by Mäkinen et al [1995b].…”
Section: Discussionmentioning
confidence: 99%
“…Since at least 1982, more than half of chewing gums have been sweetened by xylitol, often in conjunction with other sugar alco hols. There are now data available suggesting a long term cariostatic effect of xylitol chewing gum usage [Isokangas et al, 1989]. Some other 30 sweet products are sweetened with xylitol, and this sugar alcohol seems to have multiple effects on dental plaque [Soderling et al, 1989], A strong decline of caries prevalence was also re corded in the Canton of Zurich, which represents one sixth of the Swiss population.…”
Section: Two Countries With Very Strong Declines Of Caries Prevalencementioning
confidence: 98%
“…After two years, this blind study showed a mean reduction in caries in the children chewing xylitol gum of 44% compared with the control group who did not chew any gum. 18 The caries preventive effectiveness was observed three 22 and five years 26 after discontinuation of the use of xylitol -the greatest long-term preventive effect being seen on second permanent molars which erupted during the xylitol gum trial. 39 Scheie and Fejerskov, 12 in their review of this trial, point out that an important factor to be considered in the interpretation of the results was the impact that chewing xylitol gum had on decreasing the intake of conventional solid sweets during the trial and they also suggest that participation in the trial may have raised oral health awareness during the subsequent five years.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%